Risk of HBV reactivation in relapsed or refractory diffuse large B-cell lymphoma patients receiving Bruton tyrosine kinase inhibitors therapy - Ni, Ying; Gao, Lixia; Lu, Yan; Ye, Shiguang; Zhou, Lili; Qian, Wenbin; Liang, Aibin; Li, Ping (Frontiers in Immunology, 2022)
Abstract Background: Bruton tyrosine kinase inhibitors (BTKis) interrupt B-cell receptor signaling and thereby could potentially reactivate hepatitis B virus (HBV). However, data about the risk for HBV reactivation (HBVr) of BTKis in relapsed or refractory diffuse large B-cell lymphoma (R/R DLBCL) patients are sparse. Methods: A total of 55 R/R DLBCL patients receiving BTKis therapy in the Tongji Hospital of Tongji University were enrolled. Patient clinical characteristics, treatment outcomes and details of HBVr were collected and analyzed, aiming to demonstrate the risk of HBVr in R/R DLBCL patients post BTKis therapy and the efficacy of BTKis in HBV-associated R/R DLBCL patients. Results：Of 55 R/R DLBCL patients treated with ibrutinib (N=38) and zanubrutinib (N=17), 4 were with chronic HBV infection (HBsAg positive), 26 with resolved HBV infection (HBsAg negative and HBcAb positive) and 25 without HBV infection (HBsAg negative and HBcAb negative). In resolved HBV infection group, 2 patients developed HBVr after 1 month’s use of ibrutinib and 10 months’ use of zanubrutinib, respectively. Neither of them developed HBV-related hepatitis. Our finding showed that the incidence of HBVr in resolved HBV infection group was 7.69% (95% CI, 0.9-25.1%). In this study, Overall response rate (ORR) was 70.9%. 1-year overall survival (OS) rate was 80.0%. Median progression-free survival (PFS) was 4 months (95% CI, 3-5 months). In addition, HBV infection was not associated with response rates or survival among R/R DLBCL patients post BTKis treatments. Conclusion: Our study suggested that HBV infection do not affect the efficacy of BTKis’ treatment. However, R/R DLBCL patients with resolved HBV infection are at a moderate risk of developing HBVr throughout BTKis treatment. Patients should be screened for HBVr during BTKis therapy.